A soy protein enzymatic digest mitigates Nrf2-related oxidative stress and attenuates depression-like behavior in a mouse model of sub-chronic restraint stress - Takuwa Yasuda; Yasuhiro Kashima (Heliyon, 2024)
Continuous oxidative stress conditions have been identified as a major cause of various neuropsychiatric disorders, including depression. The present study investigated the potential antidepressant-like effects of a soy protein enzymatic digest (SPD) containing soy-deprestatin, which is a soy-derived peptide with reported antidepressant-like effects, as well as its ability to mitigate oxidative stress in the brain caused by sub-chronic restraint stress. Mice were divided into two groups: a control group and restraint stress group. The restraint stress group was further divided into two groups administered water or SPD. After repeated short-time restraints over five days, we evaluated immobility times in the tail suspension test, and antioxidant enzyme activities, glutathione levels, oxidative stress maker levels, and the gene expression levels of Nrf2 and antioxidant enzymes in the brain. The results obtained showed that the oral administration of SPD reduced immobility times in mice exposed to restraint stress. In comparisons with the water-treated restraint group, the administration of SPD restored superoxide dismutase, catalase, glutathione peroxidase, and glutathione reductase activities and glutathione levels and prevented restraint stress-induced increases in malondialdehyde, carbonyl protein, and 8-OHdG levels in the restraint stress group. In addition, high expression levels of Nrf2, HO-1, NQO-1 and GCLC were observed in the SPD-treated restraint group. These results suggest that SPD attenuated repeated restraint stress-induced depression-like behaviors by mitigating oxidative stress through the activation of the Nrf2 signaling pathway.